Cities and their networks in EU-Africa migration policy: Are they really game changers? - Steffen Angenendt; Nadine Biehler; David Kipp (Stiftung Wissenschaft und Politik (SWP), 2021)
The international debate on migration policy increasingly views cities as game changers since cities have to find rapid, efficient, and lasting solutions to problems relating to forced displacement and migration. However, this assessment also has its critics. From a European perspective, cooperating with African cities is important because migration from Africa is expected to rise in the short and medium term. From an African perspective, there is a wish to extend the potential for legal migration and for intercontinental mobility. Existing cooperation between African and European cities shows that the actors involved pursue very different objectives. Their potential for participation is limited but simultaneously highly dependent on political will and context. In order to make use of cities' potential for cooperation, particularly in shaping legal migration, cooperation instruments must be designed in such a way as to give cities adequate funding and sufficient powers. Divisions between urban and rural areas should not be deepened, and social conflicts should not be exacerbated. Public funds should be used preferentially to support existing networks, especially those of small and medium-sized cities; such cities should be involved above all in the shaping of labour mobility and migration and in the reception of refugees. Philanthropic funding of cities and city networks can also be helpful in harnessing the potential of municipal actors.
Keywords: 300; Migrationspolitik; Internationale Zusammenarbeit; Netzwerk; Stadt; Afrika; Europa